A STUDY ON EFFICIENT MICROORGANISMS ISOLATED FOR DEGRADATION FROM MUNICIPAL SOLID WASTE OF CHHATRAPATI SAMBHAJINAGAR, MAHARASHTRA, INDIA - Thorat, Abhijit; Ingale, Rakshanda; Rakte, Vijay; Sangle, Ketki; Thorat, Sanjaykumar (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
With rapid industrial development and the progress of civilization, the problem of increased waste generation has become more complex in urban areas. This research evaluates the composition and characteristics of municipal solid Waste produced in a representative residential neighbourhood. Ten samples were taken from the disposal site of the Chhatrapati—Sambhajinagar (Aurangabad) city area. Gathered from garbage, nine bacterial isolates were made using a nutrient agar medium. Investigations were conducted into the best culture conditions, microbiological traits, biochemical traits within the strains, tolerance to five heavy metals (Cadmium, zinc, Arsenic, lead and mercury), sensitivity to four different antibiotics (penicillin, streptomycin, oxytetracycline, and gentamycin), and extracellular enzyme production of the microbial strains. All six strains that could produce protease were used for the waste degradation efficiency test. Due to these findings, there is now a greater chance of identifying bacteria of scientific significance from municipal waste disposal sites, and these isolates may be a key source of compounds with practical applications in industry. Based on the research, it is possible to extract beneficial bacteria for the environmentally friendly bioconversion of solid Waste from the (Chhatrapati. Sambhajinagar (Aurangabad) city area. JEL Classification Codes: G32, F65, L66, L25, M41.